Overview of Compliance with Payment of Employment Social Security Contributions for the Wage Recipient Segment and Its Improvement Strategy - Riana Harumi Putri; Sri Hartini (Jurnal Indonesia Sosial Teknologi, 2024)
Employment social security in Indonesia must be followed by everyone who works, including foreigners who work for at least 6 months in Indonesia. In the Wage Recipient (PU) membership segment, Employers are required to register and pay their labor contributions to the Social Security Administration Agency (BPJS) Employment. Employers are required to pay employment social security contributions no later than the 15th of the following month after the period of contributions billed. There are still employers who do not comply in terms of paying employment social security contributions which hurts their workforce. Therefore, BPJS Employment seeks to increase compliance with the payment of contributions of Wage Recipient Participants so that workers get maximum employment social security services. This study aims to provide an overview of the compliance of employment social security contributions by employers and the efforts made by BPJS Employment in improving compliance with contribution payments. The research method used is descriptive analysis with secondary data sources in the form of BPJS Employment reports and literature studies. Based on the results of the study, on average per month 18% of employers do not comply with paying employment social security contributions. The strategy carried out by BPJS Ketenagakerjaan is to increase compliance with contribution payments by employers through participant coaching, improving service quality, and the audit supervision process.